To integrate x^(-x), we can use the technique of integration by parts. The formula for integration by parts is:
∫ u * dv = u * v - ∫ v * du,
where u and v are functions of x, and du and dv are their respective differentials.
Let's choose u = x^(-x) and dv = dx. Taking the differentials of both sides, we have du = (-x * x^(-x-1))dx and v = ∫dv = ∫dx = x.
Using the formula for integration by parts, we can rewrite the integral as:
∫ x^(-x)dx = ∫ u * dv = u * v - ∫ v * du
= x^(-x) * x - ∫ x * (-x * x^(-x-1))dx.
Simplifying this expression, we get:
∫ x^(-x)dx = x^(1-x) + ∫ x^(2-x)dx.
Now we need to integrate ∫ x^(2-x)dx. We can rewrite this as:
∫ x^(2-x)dx = ∫ (x^2 * x^(-x))dx = ∫ (x^2 * e^(-x * ln(x)))dx,
where we have used the fact that x^(-x) can be written as e^(-x * ln(x)).
This integral does not have a simple closed form solution and requires numerical methods or special functions to evaluate.
Therefore, the final result for the integral is:
∫ x^(-x)dx = x^(1-x) + ∫ x^(2-x)dx.
Intergrate x^-x
1 answer